Students with disability and the quest for inclusive education: A case study of private schools in greater Cairo - Sayed-Ahmed, Noha (AUC Knowledge Fountain, 2016)
Continuing acts of marginalization and discrimination against children with disability in education are undeniable, especially in developing countries. These acts of discrimination raise concerns regarding legislative reforms that are essential to enforce inclusive education in schools. This research investigates the extent to which private schools in Egypt are inclusive for students with disability by seeking the inputs from the main stakeholders; school administrators, teachers, and parents. Findings of the research show that despite the enthusiasm and good intentions of all parties, implementing inclusive education in Egyptian private primary schools is still at unsatisfactory levels. Thus, recommendations focus on providing adequate funding resources, designing enabling inclusive legislations, enhancing support services, providing relevant educational tools, and providing efficient training programs for teachers and school administrators. These recommendations seek to enhance the inclusiveness of the education system in Egypt and other developing countries.